The “Target Sign” in a 46-Year-Old Patient with COVID-19 Pneumonia - Alexandra Pérez Pérez; Rahul Lazarus; Anju Dubey (Case Reports in Radiology)
COVID-19 has various imaging manifestations, most commonly peripheral ground-glass opacities with a basilar posterior predominance. Less common imaging manifestations include consolidations, findings typical of organizing pneumonia, such as “halo” or a “reverse halo” sign, and vascular enlargement. Our case describes a “target sign” on CT, which is uncommon but is increasingly being recognized. The target sign consists of a central nodular opacity with surrounding ground-glass opacity, then a surrounding relatively lucent ring, and a more peripheral ring of consolidation or ground-glass opacification. This may be the sequela of focal vascular enlargement, endothelial injury, microangiopathy, and perivascular inflammation. The case described involves a 46-year-old male who presented with subjective fevers, nonproductive cough, and hypoxia, subsequently diagnosed with COVID-19. CT imaging performed as part of initial work-up revealed multifocal ground-glass opacities scattered throughout the lung parenchyma, as well as multiple target sign lesions. Although it is a rare finding, the target sign, when present, may suggest the diagnosis of COVID-19.